The Effects of Displacing Sedentary Behavior With Two Distinct Patterns of Light Activity on Health Outcomes in Older Adults (Implications for COVID-19 Quarantine) - Grant, Dale; Tomlinson, David; Tsintzas, Kostas; Kolić, Petra; Onambele-Pearson, Gladys Leopoldine (Frontiers in Physiology, 2020)
Rationale: The COVID-19 pandemic is limiting outdoor and community-based activities especially for older adults owing to the requirement for self-isolation, potentially increasing prolonged sedentary behaviour (SB). Given a poor tolerance for intense exercise, SB displacement with light intensity physical activity (LIPA) is a promising health enhancing alternative. Therefore, the aims of this study were to investigate the effects of two different types of SB displacement on health outcomes in older adults, and any differential impact of associated LIPA pattern. Method: Twenty-eight older females (age: 73±5y, height: 1.60±0.07m, weight: 67±10kg, BMI: 26.1±3.6 kg/m2) underwent overnight fasted DEXA imaging, blood sampling, and functional assessments before being randomly allocated to one of two groups: 1) Single continuous bout of 45-50min LIPA daily (n=14); or 2) Sedentary behaviour fragmentation (SBF) ( 48 mins LIPA daily, 2mins LIPA for every 30mins of SB) (n=14). Compliance was systematically monitored using tri-axial accelerometery. All measures were taken at weeks 0 and 8. Results: Physical behaviour significantly altered (decreased SB/ increased LIPA) (p<0.05), and to a similar extent in both groups. We observed a significant reduction in serum triglycerides [p=0.045, Effect size (ɳp2)=0.15] [SBF: -0.26±0.77mmol/L, LIPA: -0.26±0.51mmol/L], improved 30 second sit-to-stand count (p=0.002, ɳp2=0.32, 2±3 STS’s) and speed (p=0.009, ɳp2=0.35, -10±33%), as well as increased average handgrip strength (p=0.001, ɳp2=0.45, 6±12%), and gait speed (p=0.005, ɳp2=0.27, 0.09±0.16m/s) in both groups. Interestingly, SBF caused a greater increase in peak handgrip strength (8±14%), compared to LIPA (2±10%) (p=0.04, ɳp2=0.38). Conclusion: SB displacement induced significant improvements in fasting triglycerides, gait speed, as-well as sit-to-stand endurance/ speed in older adult females. Frequent vs continuous SB displacement also caused greater increases in handgrip strength. Whilst both SB displacement protocols display promise as efficacious home-based interventions for self-isolating older adults, our results would suggest a physical functioning advantage of the SBF protocol for certain outcomes.